Evaluación de un biocida obtenido a base de extractos etanólicos de la hoja de tabaco (Nicotiana Tabacum) para el control de Penicillium SPP. (2025)
Because, at present, the excessive use of agrochemicals and synthetic pesticides is a global problem that affects public health and the environment, thus generating a predominance of cases of acute poisoning, preventing the need to preserve and maintain post-harvest products. The present work proposes the study of an alternative to the use of pesticides, specifically synthetic fungicides, generating the use of a natural resource such as tobacco leaf (Nicotiana tabacum), which presents different active components for the inhibition of different pathogenic microorganisms such as Penicillium spp. First, the solid-liquid extraction process was optimized using different methods (Soxhlet, cold maceration, simple distillation and reflux), selecting the method with the highest yield and identifying the bioactive compounds such as alkaloids, flavonoids and tannins present in the extract. Following this, in vitro assays were performed to determine the antifungal activity of the extract using minimum inhibitory concentration (MIC) tests and agar wells, demonstrating its antifungal activity in inhibiting the growth of Penicillium spp.